2006
DOI: 10.1523/jneurosci.4469-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vasotocin and Mesotocin Stimulate the Biosynthesis of Neurosteroids in the Frog Brain

Abstract: The stimulatory effect of VT and MT on neurosteroid biosynthesis was mimicked by VP and OT, as well as by a selective V1b receptor agonist, whereas V2 and OT receptor agonists had no effect. VT-induced neurosteroid production was completely suppressed by selective V1a receptor antagonists and was not affected by V2 and OT receptor antagonists. Concurrently, the effect of MT on neurosteroidogenesis was markedly attenuated by selective OT and V1a receptor antagonists but not by a V2 antagonist. The present study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 76 publications
1
46
0
Order By: Relevance
“…hCG increases circulating androgens, which are necessary for calling [64], and sex steroid treatment restores brain AVT concentrations and calling in castrated male anurans [6,42]. In addition, do-Rego et al [14] reported that AVT stimulates neurosteroid synthesis in the frog brain. However, Yang et al [70] recently reported that hCG treatment directly activates luteinizing hormone receptors in brain areas involved in call production in androgen-primed male X. laevis.…”
Section: Discussionmentioning
confidence: 99%
“…hCG increases circulating androgens, which are necessary for calling [64], and sex steroid treatment restores brain AVT concentrations and calling in castrated male anurans [6,42]. In addition, do-Rego et al [14] reported that AVT stimulates neurosteroid synthesis in the frog brain. However, Yang et al [70] recently reported that hCG treatment directly activates luteinizing hormone receptors in brain areas involved in call production in androgen-primed male X. laevis.…”
Section: Discussionmentioning
confidence: 99%
“…We have also detected V1a receptor expression in the Mauthner cells located at the level of the VIII cranial nerve root in the medulla oblongata; this is thought to be involved in the tail-vibrating behavior of the male newt during courtship (Iwata et al 2000) suggesting that AVT directly modulates Mauthner cell activity. Do-Rego et al (2006) have recently demonstrated that AVT and mesotocin stimulate the biosynthesis of neurosteroids in the frog R. esculenta. In C. pyrrhogaster, immunoreactive cells for cytochrome P450 side-chain cleavage enzyme and 3β-hydroxysteroid dehydrogenase, both of which are key enzymes for steroidogenesis, are found in the anterior preoptic area and magnocellular preoptic nucleus (Inai et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…they are capable of converting cholesterol into various neurosteroids. It has also been demonstrated that, in the frog brain, the biosynthesis of neurosteroids is finely regulated by GABA (Do Rego et al, 2000), several endozepines (Do Rego et al, 1998, 2007b, neuropeptide Y (Beaujean et al, 2002) and arginine vasotocin (Do Rego et al, 2006), suggesting that neurosteroids may mediate some of the central effects of neurotransmitters and neuropeptides. However, all these studies have been conducted in adult frogs and, up to now, nothing is known regarding the biosynthesis of steroids in the brain of tadpoles.…”
Section: Introductionmentioning
confidence: 99%